PENDIDIKAN KARAKTER MANDIRI MELALUI PEMBELAJARAN PKn DAN BUDAYA SEKOLAH (STUDI KASUS) DI SMK NEGERI 2 BANJARMASIN - Eti Lindasari (JURNAL SOCIUS, 2019)
AbstractEducation is an important important thing that can produce children who are smart and well behaved. Behave well related to aspects of attitudes and morality built through education to enhance the potential of self-educated learners the values, attitudes and morals to shape the characters. Independent character is necessary because the development of global society and various information requires the power of society, individuals, and learners to choose appropriately positive information. Independent character is required for students to equip themselves able to compete to face the media challenge seen as an indication of moral decline, independent character such as cheat action, search for exam answers, research aimed at analyzing independent character education implemented through Civic learning and character independent education through school culture. Research uses qualitative research methods. Research location at SMK Negeri 2 in Banjarmasin South Kalimantan. Techniques of collecting interview data, observation, documentation. Data analysis techniques qualitative data analysis that is data collection, summarize, select data, data presentation, conclusion, data verification. The results of the study for self-character education through learning Civics carried out necessary planning from the beginning, planned in an organized curriculum program according to Curriculum 2013. Implementation of learning Civic teachers conducted 83.48%. Self-learning activities of students reached 75%. The program planning of extracurricular activities of independent character education carried out the deputy head of student affairs, counselor of OSIS, extracurricular. Researchers suggest improving teacher management through IHT, workshops, technical guidance.Keywords: Education, Self  Character, Civic Learning, School Culture.AbstrakPendidikan merupakan hal penting yang penting yang dapat menghasilkan anak yang cerdas sekaligus berperilaku baik. Berperilaku baik berhubungan dengan aspek sikap dan moralitas dibangun melalui pendidikan untuk meningkatkan potensi diri peserta didik pendidikan nilai-nilai, sikap dan moral untuk membentuk karakter. Karakter mandiri diperlukan karena perkembangan masyarakat global dan berbagai informasi memerlukan kekuatan masyarakat, individu, dan peserta didik  untuk memilih dengan tepat informasi positif.  Karakter mandiri diperlukan peserta didik membekali diri mampu bersaing menghadapi tantangan media terlihat indikasi penurunan moral, karakter mandiri seperti tindakan menyontek, mencari jawaban ujian, penelitian bertujuan menganalisis pendidikan karakter mandiri yang dilaksanakan melalui pembelajaran PKn dan pendidikan karakter mandiri melalui budaya sekolah. Penelitian meggunakan metode penelitian kualitatif. Lokasi penelitian di SMK Negeri 2 di Banjarmasin Kalimantan Selatan. Teknik pengumpulan data wawancara, observasi, dokumentasi. Teknik analisis data analisis data kualitatif yaitu pengumpulan data, merangkum, memilih data, penyajian data, penarikan kesimpulan, verifikasi data. Hasil penelitian agar pendidikan karakter mandiri melalui pembelajaran PKn dilaksanakan diperlukan perencanaan sejak awal, direncanakan secara tertata program kurikulum sesuai Kurikulum 2013. Pelaksanaan pembelajaran PKn dilakukan guru hasil 83,48%. Aktifitas belajar peserta didik mandiri tercapai 75%. Perencanaan program kegiatan ekstrakurikuler pendidikan karakter mandiri dilaksanakan wakil kepala seko;ah urusan kepeserta didikan, Pembina OSIS, ekstrakurikuler. Peneliti menyarankan peningkatan pegelolaan pembelajaran guru melalui IHT, workshop, bimbingan teknis.Kata Kunci: Pendidikan, Karakter Mandiri, Pembelajaran PKn, Budaya Sekolah.